La resolución unilateral de los contratos administrativos: consecuencias económicas en la contratación pública peruana - Rodas Ubillús, Roberto Carlo (2009)
The present Thesis to choose the Attorney's Title, is orientated to needthe existence of the administrative contract, and as consequence of the same one, of the existence of a set of exorbitant legal authorities to the Private Law, and inside these, of the study of the unilateral resolution of the administrative contract, and his economic implications. It is important to add, that the Public Administration is in the faculty to help, the subject matter of the contractual unilateral resolution, when the breach takes place(is produced), on the part of the suppliers and / or the contractor. But this legal authority is not discretionary, is fastened initially of Legality, Transparency, in the public management. Nevertheless this right admits to the unilateral contractual resolution that it has the Public Administration, the thesis orientates to indicate to him(you,them), that it does not exist in the operators of the contractual administrative norm, quality and efficiency, in the exercise of this one legal authority, which often for negligence, cohabitation, is generating negative impact in the economía of the public entities, fundamentally: for transgression to the due procedure, deficient production of the technical processes, inadequate management in the processes of control for level pre - contractual, contractual and of execution, as well as also deficient liquidation of the works and application of the punishment established and regulated by the Law